Drought response in plus trees of Teak (Tectona grandis Linn.f.) provenances of Kerala - Mohammed Ali Eltoum Hassan (Department of Forest biology and tree improvement, Vellanikkara, 2020)
ABSTRACT A study on ‘Drought response in plus trees of teak (Tectona grandis Linn. f.) provenances of Kerala’ was conducted in College of Forestry, Vellanikkara during 2018-2019 to evaluate variability in seedling biometric, physiological and biochemical characters of plant during drought stress and drought recovery. Drought stress was induced by withholding water till leaves exhibited symptoms of wilting. Plantlets were exposed to two consecutive drought treatments with an intervening period of stress relief through rehydration. Seedling vigor was screened at six months. No variability was present in morphometric characters like height, diameter, number of leaves and branches. After inducing drought stress, growth parameters slowed down in all accessions between plus trees. Induction of drought resulted in reduction in most of the physiological parameters of the plantlets of teak plus tree accessions. Relative water content, photosynthetic rate, stomatal conductance, transpiration rate, chlorophyll a, chlorophyll b, total chlorophyll and chlorophyll stability index showed reduction. However, under drought stress, plantlets showed increased of canopy air temperature differences and cell membrane stability index. Most of biochemical parameters like free amino acid, proline, glycine betaine, total soluble sugar, super oxide dismutase, peroxidase and malondialdehyde increased after inducing drought. However, total soluble protein and nitrate decreased under drought induction. After rehydration, most of these physiological and biochemical parameters rapidly returned to the level of normal irrigated condition. The stomatal conductance was only differed in the accessions before stress was induced. However, after stress, it was found that accessions differed in stomatal conductance, photosynthetic pigments and total chlorophyll content. In drought recovery, there was no variation in physiological parameters among accessions. Variability on biochemical characters were observed in nitrate reductase, free amino acid, proline and peroxidase among accessions during pre-stress stage, while in drought stress it was observed that proline, super oxide dismutase, peroxidase and 139 malondialdehyde differed among accession. In drought recovery, characters such as nitrate reductase, free amino acid, proline and peroxidase showed variability. Correlation studies showed that among the physiological and biochemical character only chlorophyll a, chlorophyll b and total chlorophyll showed positive correlation with the number of leaves during drought stress, while in recovery, positive correlation was shown by super oxide dismutase, chlorophyll a, chlorophyll b and total chlorophyll content and negative correlation was observed in photosynthetic rate, transpiration, relative water content and stomatal conductance. Hierarchical cluster analysis was done for the eleven accessions based on the Euclidian squared distance. During drought stress, the accessions grouped into five clusters; cluster III possesses four of accessions whereas the least number observed for the cluster V. In recovery, it was grouped into seven clusters; cluster VII had three accessions, while only one accession was present in cluster I, IV, V and VI. First two components of principle component analysis during drought stress accounted for 41.9 per cent of the total variability, which was mainly contributed positively by relative water content, nitrate reductase, free amino acid, proline and malondialdehyde. In drought recovery, first two components of PCA together accounted for 53.2 per cent of the total variability, which was mainly contributed positively by photosynthetic rate, stomatal conductance, transpiration rate, chlorophyll stability index, glycine betaine and malondiadehyde. Selection index were worked out to select accession tolerant to drought stress and recovery based on biochemical parameter and chlorophyll content using first principle component as index. It was found that KFRI T55 was most tolerant and quickest to recover after reliving stress among accession. It can be concluded from the results that physiological and biochemical variations exist in teak plus tree accessions. These results could be useful in selection of drought tolerant